Predictive Value of Systemic Inflammatory Markers in the Prognosis of Prostate Cancer with Variant Histology - Ates, Huseyin Aytac; Aktas, Semih; Araci, Muhammet Hilmi Enes; Okucu, Emrah; Yalcin, Berrin; Koseoglu, Hikmet (Urology Journal, 2025)
Objective: This study aimed to investigate the potential role of systemic inflammatory markers in the management of Prostate Cancer (PCA) with variant pathology. Materials and Methods: A retrospective analysis was conducted on 302 patients who underwent radical prostatectomy between 2014 and 2023. After applying exclusion criteria, 279 patients were included: 207 with adenocarcinoma and 72 with variant pathologies. Systemic inflammatory markers such as Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), Systemic Immune-Inflammation Index (SII), and Systemic Inflammation Response Index (SIRI) were compared between the groups. Results: Patients in the variant group were significantly older (p = 0.005). The frequencies of lymphovascular invasion (LVI), perineural invasion (PNI), and positive surgical margins (SM) were significantly higher in the variant histology group (p < 0.001, p = 0.014, and p < 0.001, respectively), as were ISUP grades (p < 0.001). Pretreatment PSA values were also significantly higher in the variant group (p < 0.001), as was the rate of subsequent radiotherapy (p < 0.001). However, no significant differences were found in NLR, PLR, SIRI, or SII values between the groups. Recurrence rates were significantly higher in the variant group (p < 0.05), but overall mortality did not differ. Conclusion: Systemic inflammation markers have limited value in predicting prognosis among patients with variant PCA. This highlights the complex role of inflammation in cancer progression and underscores the need for further research to identify more specific biomarkers for different PCA variants.